STUDI ANALISIS KURIKULUM ILMU FALAK UIN ALAUDDIN MAKASSAR BERBASIS INTEGRASI ASTRONOMI - Primantyas, Bagus Herdianto; Wakia, Nurul; HR, Sabriadi (Universitas Islam Negeri Alauddin Makassar, 2026)
ABSTRACT This research focuses on analyzing the curriculum of phalac science at the State Islamic University of Alauddin Makassar based on astronomy integration. The formulation of this problem includes: how is the curriculum of phalac science at Alauddin Makassar State Islamic University, how is the astronomical integration of the curriculum of phalac science at Alauddin Makassar State Islamic University. This research uses a library research method by analyzing the astronomy integration-based astrophysics curriculum through sources obtained from books, articles, theses, and reports on previous research results that are relevant to this research. The results of this study are the realistic learning of astrophysics applied by the Falak Science Study Program at Alauddin Makassar State Islamic University has 63 courses with 147 credits consisting of 13 University compulsory courses, 22 Faculty courses and 26 Falak Science Study Program courses. Of the 26 courses in the Falak Science Study Program that need to be added are 13 courses, namely Lunar Eclipse Hisab, Solar Eclipse Hisab, Non-Optic Rukyat Devices, Optical Rukyat Devices, Advanced Falak Science Text Studies, Hisab and Rukyat Practices, Basics of Astronomy, Basics of Spherical Astronomy, Basics of Physics, Mathematics. Hisab Rukyat Study of Different Countries, Astronomy and Culture, Calculator Algorithms and Programming, Computer Algorithms and Programming (Excel), Computer Algorithms and Programming (VB and Android), and Statistics. The implication of this research is that the Falak Science Study Program is expected to reduce legal courses to fit the focus of the academic field and review or review the existing curriculum at other universities.